2020
DOI: 10.3989/scimar.05007.01a
|View full text |Cite
|
Sign up to set email alerts
|

Potential biomass and distribution of octopus in the eastern part of the Campeche Bank (Yucatán, Mexico)

Abstract: The octopus fishery on the Campeche Bank (Yucatán, Mexico) is considered the third largest in the world. In Yucatán, two fleets target this resource: an artisanal fleet and a semi-industrial fleet. The artisanal fleet only catches Octopus maya, while the semi-industrial fleet catches two species, O. Maya and O. “vulgaris” Type II, because it operates at deeper waters ( > 30 m). Since there is no information on the abundance of O. “vulgaris” Type II, management is based only on O. Maya. In order to generate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
(70 reference statements)
1
10
0
Order By: Relevance
“…Having a planktonic phase would allow this species to undertake vertical migrations and be at the mercy of the currents for later settling in distant areas (Santana‐Cisneros, Ardisson, et al, 2021). This scenario provides arguments to think that individuals of this species could come from the Caribbean Sea and that their recruitment would occur in the eastern part of the Yucatan Shelf as recently hypothesized (Avendaño, Hernández‐Flores, et al, 2020) and in concordance with a hatching period mainly occurring from January to July (Velázquez‐Abunader, 2019).…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Having a planktonic phase would allow this species to undertake vertical migrations and be at the mercy of the currents for later settling in distant areas (Santana‐Cisneros, Ardisson, et al, 2021). This scenario provides arguments to think that individuals of this species could come from the Caribbean Sea and that their recruitment would occur in the eastern part of the Yucatan Shelf as recently hypothesized (Avendaño, Hernández‐Flores, et al, 2020) and in concordance with a hatching period mainly occurring from January to July (Velázquez‐Abunader, 2019).…”
Section: Introductionsupporting
confidence: 66%
“…Historically, it has been thought that depth was the factor that determined the abundance of O. americanus and O. maya in the Campeche Bank, the two main species that support the octopus' fishery in the south‐eastern Gulf of Mexico (DOF, 2018). However, recent studies have suggested that both species can co‐occur at depths between 25 and 45 m (Avendaño et al, 2019; Avendaño, Hernández‐Flores, et al, 2020). The results of this work confirm that, though the scenario seems to be more complex with maximum overlap restricted to the eastern part of the fishing ground, the distribution of abundance for both species differs to the west and along the coastal‐ocean axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where the two species overlap in geographic range, juvenile and adult O. insularis tend to be found on shallower (0.5-40 m) reef and rocky substrates in warmer water (Leite et al 2009;Rosas-Luis et al 2019), while juvenile and adult O. americanus are found up to 200 m in cooler waters on rock, rubble, shell beds or on the interface between rock and sand (Lima et al 2017;Avendaño et al 2020b). In subtropical regions, where shallow areas are typically less than 24°C throughout the year, O. insularis is less common, although its range may shift due to climate change (Ángeles-González et al 2020;Lima et al 2020a).…”
Section: Differences In Habitatmentioning
confidence: 99%
“…The characteristics of the upwelling area in our study also raise the possibility that it could be a suitable area for a “larval nursery” and, therefore, associated with larger settlement (Butler et al, 2006). A recent study reported adult presence in these areas (Avendaño, Hernández‐Flores et al, 2020).…”
Section: Discussionmentioning
confidence: 94%